Challenges of Human Resources Management in Project-based Organizations - Attaullah Jawad; Hameedullah Noori (Randwick International of Education and Linguistics Science Journal, 2021)
Organizations are constantly under the influence of the environment they are operating in. The Industrial Revolution necessitated the establishment of long-lasting organizations with an emphasis on the stability of activities. However, undermining this principle, today’s businesses and organizations have moved towards projectification. This has demoted permanent and long-lasting activities in task-oriented organizations and transformed the meaning of many concepts such as financial management, human resource management, and knowledge management. Human resources management (HRM) is one of the areas of management that has undergone major changes in project-based organizations (PBOs). Since this new nature of organizations and businesses has challenged the stability of HRM, PBOs must plan and develop alternative methods for HRM. This paper hence aims to introduce the concept of PBOs and different types of PBOs and then discuss how this new organizational structure affects and challenges HRM.